Drinking and Neighborhood Contexts of Alcohol's Harms from Others. (16th March 2021) - Tam, Christina C; Karriker-Jaffe, Katherine J; Greenfield, Thomas K
Abstract: Aims: Negative consequences of alcohol (or secondhand effects) extend beyond drinkers to affect other people, including both known others (friends, family members, spouses/partners) and strangers. Secondhand effects of alcohol manifest across various social environments, including the places where people drink and the neighborhoods where they live. These neighborhoods are characterized by different levels of alcohol availability and degrees of residential social cohesion. Hence, social environments may confer risk or protect from harms from others' drinking. The current study explores: (a) how drinking venues and neighborhood contexts relate to harms from other people's drinking (both known others and strangers), and (b) whether these associations vary by gender. Methods: Using pooled data from the National Alcohol Survey and National Alcohol's Harms to Others Survey ( N  = 5425), we regressed harms from various drinking others on social environment characteristics (drinking venues, alcohol availability and social cohesion) for the full sample and separately by gender. We used the false discovery rate method to adjust for multiple testing. Results: Overall, greater neighborhood social cohesion was associated with lower odds of harm from drinking others and, specifically, harm from drinking strangers. The effect of social cohesion was most pronounced for men. Conclusions: Social cohesion was the most salient neighborhood factor associated with reduced alcohol-related harms from strangers. Directions for future research and policies to mitigate these harms are discussed. Abstract : Short Summary : Social cohesion protected against harm from drinking strangers in the full sample. Gender-stratified analyses showed social cohesion had the most pronounced effect for men.